The Implementation of Problem-Based Learning Method with Video Media to Increase Learning Activity in The Thematic Learning of Students In Elementary School - Titik Rusniwati (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2022)
The purpose of this study was to analyze the implementation of the Problem Based Learning (PBL) method with video to improve learning activities in thematic learning for fourth grade students at SDN 23 Sungai Raya and describe learning activities in thematic learning using the PBL method with video media. The research method used in this study was a descriptive method. The subjects of this study were the teacher as a researcher in first grade and fourth grade students at SDN 23 Sungai Raya, totaling 22 students, 12 girls and 10 boys. The research procedure for implementing thematic learning using video media goes through four stages: a) planning, b) implementation, c) reflection and d) evaluation. The data collection technique used was the direct observation technique, with the data collection tool in an observation sheet. The results showed an increase in the ability of teachers to develop lesson plans and implement learning in thematic lessons using the PBL method with video media for first-grade students at SDN IV Sungai Raya and an increase in activities in thematic learning using the PBL method with video media for elementary students. In the first cycle of 69.69%, there was an increase in the value in the second cycle of 90.90%, mental activity increased, the first cycle was 57.54% and the second cycle was 93.94, the emotional activity in the 80, 68% in the first cycle to 95.45% in the second cycle.